Pengaruh Layanan Bimbingan Kelompok dengan Teknik Modelling terhadap Motivasi Belajar Siswa : The Influence of Group Guidance Services with Modeling Techniques on Student Learning Motivation - Ayu Rahmawati Siregar; Saiful Akhyar Lubis (ITScience (Information Technology and Science), 2025)
The purpose of this study was to examine the effect of using modeling techniques in improving students' learning motivation through group guidance services for class VIII students of SMP Muhammadiyah 57 Medan. The researcher applied a quantitative approach to measure the effect of treatment objectively through data that can be analyzed statistically. The type of research used was pre-experimental. The design chosen in this study was a one-group pretest-posttest design, which is a design involving one group that is given a pretest before treatment and a posttest after treatment, allowing researchers to observe changes or improvements that occur after the intervention is carried out. The population in this study consisted of all class VIII students, totaling 110 students, while the sample taken was 8 students with low levels of learning motivation. The sample collection technique used was non-probability sampling, especially purposive sampling. Data collection was carried out with a learning motivation scale. The analysis requirement test applied in the study as a requirement for this parametric statistical analysis was the Normality Test, Homogeneity Test, and Paired sample t-test, with a significance level of 5%. The results of the analysis showed the Asymp value. Sig (2-tailed) of 0.000 < 0.05. So, there is a real difference between the mean of the learning motivation indicator in the pretest and posttest (2-tailed), which is 0.000 < 0.005, which means that Ha is accepted and Ho is rejected. After the implementation of group guidance with modeling techniques, there was an increase. In this regard, group guidance services with modeling techniques affect increasing learning motivation in class VIII students of SMP Muhammadiyah 57 Medan.